Assessment of the Efficiency of Government Licensing Services in Supporting the Development of Micro and Small Enterprises - Hardyansah, Rommy (Bulletin of Science, Technology and Society, 2023)
The development of micro and small enterprises (UMK) has an important role in economic growth and job creation. However, one of the main obstacles faced by MSEs is the government licensing process which is often slow and complex. This research aims to evaluate the efficiency of government licensing services in supporting the development of MSEs. This research methodology includes a qualitative descriptive model. The data collected was analyzed using various efficiency indicators, including licensing processing time, costs, service quality, and level of satisfaction of MSE owners. The research results show that the government licensing process still has many challenges in supporting the development of MSEs. Licensing processing times tend to be slow, costs are sometimes high, and service quality has not reached expected standards. The level of satisfaction of MSE owners with licensing services is also relatively low.